Prone Position Effects in the Treatment of Covid-19 Patients - Farzad Rahmani; Shiva Salmasi; Parisa Rezaeifar (Babol University of Medical Sciences, 2020)
Prone positioning is a conventional method to enhance oxygenation in Acute Respiratory Distress Syndrome (ARDS) patients who need mechanical ventilator . It is proven that oxygenation is significantly more beneficial in prone position compared to the supine position. Furthermore, numerous evidences have confirmed that prone positioning could prevent lung injuries caused by ventilators